Multilayer Control of B Cell Activation by the B Cell Antigen Receptor: Following Themes Initiated With Bill Paul - DeFranco, Anthony L. (Frontiers in Immunology, 2018)
This article describes the work I did in Bill Paul’s lab as a postdoctoral fellow between 1979 and 1983, and to a lesser extent puts that work in the context of other work on B cell activation and antibody responses that was going on in Bill’s lab at that time and shortly beforehand, including the discovery of interleukin 4. In addition, this work describes the subsequent and continuing work in my own lab following up on themes I began during my time working directly with Bill. A particular emphasis was on understanding the biochemical mechanisms of signaling by the BCR to the interior of the B cell. Some of the studies from my lab related to the regulation of BCR signaling by Lyn are described in relationship to the lymphocyte tuning hypothesis put forth by Grossman and Paul in 1992 and subsequently.